ANTESEDEN DAN KONSEKUENSI KOMUNITAS MEREK PMI - Marinda Dwi Widiastari; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the perceived quality of the brand community psychological expectation. The uniquness of a brand is influenced by the psychological understanding of the brand community. A high psychological understanding of the brand community can affect positive word of mouth communication. Data collection was obtained through a questionnaire distributed to members of the PMI Surakarta blood donor community, which consisted of 200 questionnaires. This hypothesis test uses SEM (Structural Equation Modeling) analysis with the path analysis method. The result show that perceived quality has a positive effect on the psychological understanding of brand communication, brand uniqueness has a positive effect on psychological understanding of the community, psychological understanding of brand community has a positive effect on word-of-mouth communication.